From the Gospel to the Gospels : History, Theology and Impact of the Biblical Term 'Euangelion' - Pokorný, Petr (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche., 2013)
The monograph discusses the short formulae of the 'gospel' (euangelion) as the first reflected expressions of Christian faith. They adapted the apocalyptic expectations to express the Easter experience and shaped the earliest literary Gospel (Mark). This book analyzes Gospels as texts that (re- )introduced Jesus traditions into the Christian liturgy and literature. The last chapters are devoted to the origins of the idea of Christian canon.